Central K(ATP) Channels Modulate Glucose Effectiveness in Humans and Rodents - Carey, Michelle (Diabetes, 2020)
Hyperglycemia is a potent regulator of endogenous glucose production (EGP). Loss of this “glucose effectiveness” is a major contributor to elevated plasma glucose concentrations in type 2 diabetes (T2D). K(ATP) channels in the central nervous system have been shown to regulate EGP in humans and rodents. We examined the contribution of central K(ATP) channels to glucose effectiveness. Under fixed hormonal conditions (studies using a pancreatic clamp), hyperglycemia suppressed EGP by ∼50% in both humans without diabetes and normal Sprague-Dawley rats. By contrast, antagonism of K(ATP) channels with glyburide significantly reduced the EGP-lowering effect of hyperglycemia in both humans and rats. Furthermore, the effects of glyburide on EGP and gluconeogenic enzymes were abolished in rats by intracerebroventricular administration of the K(ATP) channel agonist diazoxide. These findings indicate that about half of the suppression of EGP by hyperglycemia is mediated by central K(ATP) channels. These central mechanisms may offer a novel therapeutic target for improving glycemic control in subjects with T2D.